2017
DOI: 10.1016/j.amsu.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal adhesions: A practical review of an often overlooked entity

Abstract: Formation of intra-abdominal adhesions is a common consequence of abdomino-pelvic surgery, radiation therapy, and inflammatory processes. In a small but clinically significant proportion of patients, adhesive disease may develop, wherein adhesions lead to a variety of chronic symptoms such as abdominal distension, pain, nausea, and abnormal bowel movement pattern which can be daily, intermittent, or episodic. Due to the chronic and troublesome nature of these symptoms, adhesive disease may be life-altering in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 28 publications
1
118
0
21
Order By: Relevance
“…Concerning the later, in our study sample, the rate of adhesions among women who had a previous operation of any kind was 42% compared with 38% with those who had never had surgery. Previous studies have indicated that the frequency of peritoneal adhesions in patients with no prior surgery is approximately 10% . Our significantly higher figure is likely because the majority of these cases had concomitant endometriosis.…”
Section: Discussionmentioning
confidence: 54%
“…Concerning the later, in our study sample, the rate of adhesions among women who had a previous operation of any kind was 42% compared with 38% with those who had never had surgery. Previous studies have indicated that the frequency of peritoneal adhesions in patients with no prior surgery is approximately 10% . Our significantly higher figure is likely because the majority of these cases had concomitant endometriosis.…”
Section: Discussionmentioning
confidence: 54%
“…Тому рання діагностика та профілактична елімінація чинника запалення, який стає причиною хронічного перитоніту, є пріоритетним питанням багатьох дослідницьких центрів у світі [17,18,27,28]. Дієві методи лікування, які б давали змогу повністю відновити функціональні можливості очеревини у хворих на хронічний перитоніт, нині дуже обмежені [2][3][4][5][6][7]26]. Отже, створення оптимальної моделі хронічного перитоніту та визначення темпів прогресування фіброзу очеревини є актуальними, оскільки зможуть розв'язати питання ранньої діагностики та прогнозування перебігу захворювання.…”
Section: Discussionunclassified
“…Однак залишаються невирішеними питання щодо ранньої діагностики та прогнозування перебігу захворювання, для вирішення яких обов'язковою умовою є створення оптимальної експериментальної моделі. У сучасній науковій літературі описані моделі формування гострого розлитого перитоніту, який завершується неконтро- Мітози 9,2 ± 0,8 7,5 ± 0,6 4,1 ± 0,3 2 3,2 ± 0,1 2,3 0,8 ± 0,1 1,2,3,4 льованим запально-некротичним процесом [21,29]. Але для розв'язання питань ранньої діагностики склерозу очеревини на тлі хронічного перитоніту вони не придатні, оскільки в умовах гострого процесу відбувається гіперактивний малоконтрольований інфільтративно-некротичний процес, який не притаманний хронічному перитоніту [30].…”
Section: матеріали і методи дослідженняunclassified
“…Durante la obstrucción, incrementa la producción de metano e hidrógeno por la proliferación bacteriana, lo que conlleva a una acumulación de gas y líquido, que como consecuencia aumenta la presión intraluminal e intramural y se expresa clínicamente como distensión abdominal. 15,16 Durante las primeras 24 horas del inicio de la obstrucción, disminuye el flujo hídrico desde la luz intestinal hacia la sangre, produciendo un aumento de la secreción intestinal. 9,11 Se manifiesta con distensión abdominal, debida a la acumulación intestinal del líquido y gas, provocando un aumento en la actividad intestinal en un esfuerzo para vencer la oclusión, manifestándose con dolor abdominal tipo cólico y en ocasiones diarrea al inicio.…”
Section: Introductionunclassified
“…9,11 Se manifiesta con distensión abdominal, debida a la acumulación intestinal del líquido y gas, provocando un aumento en la actividad intestinal en un esfuerzo para vencer la oclusión, manifestándose con dolor abdominal tipo cólico y en ocasiones diarrea al inicio. 15,16 Si la presión intraluminal es bastante alta, la irrigación microvascular intestinal empieza a deteriorarse, esto provoca una alteración metabólica con pérdida de electrolitos como sodio, cloro, hidrógeno y potasio, traduciéndose en una deshidratación con hipocloremia, hipokalemia y alcalosis metabólica, finalizando con una isquemia intestinal y necrosis. 9,11 Formación de adherencias postquirúrgicas: El proceso constituye una interacción compleja de eventos bioquímicos involucrados en la inflamación, reparación tisular, angiogénesis e inervación.…”
Section: Introductionunclassified